Population dynamics and stock assessment of Oreochromis niloticus (Linnaeus) in the Kaptai Reservoir, Bangladesh - Ahmed, K K U; Amin, S M N; Haldar, G C; Dewan, S (Indian Journal of Fisheries, 2011)
Population parameters of Oreochromis niloticus (Linnaeus) was estimated using FiSAT software with length-frequency data collected from Kaptai Reservoir, Bangladesh. The von Bertalanffy growth parameters L and K of the species were 55.59 cm and 0.39/yr respectively. The annual rate of natural (M) and fishing mortality (F) were found to be 0.80 and 0.59 respectively. The estimatedvalues for the exploitation rate (E) using the length converted catch curve and virtual population analysis were 0.42 and 0.258 respectively. Recruitment of this species was continuous with one peak per year. Emax was found to be 0.63. The present investigation clearly showed the under fishing (E